Exploring the Expert Group Cooperative Learning Model for Arabic Qirā’ah Material Acquisition - Nuraeni, Maya; Al-Houdy, Mohammed Ismael (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
Students' ability to pronounce sentences and determine meaning is still an obstacle in learning to read linguistic and non-linguistic Arabic. This study aimed to determine how effectively students learn to read before and after using the "Expert Group" method for class VIII students at MTs Plus Al Fath Klaten. The method used in this research is a quasi-experimental method with one one-group design that compares the pre-test and post-test. Data collection methods include observation, interviews, tests, and documentation. The sample in this study was class VIII, with a sample of 22 students and a pre-test and post-test design. The results of this study indicate that the ability to learn qiraah before applying the Expert Group method is amply demonstrated by obtaining an average score of 75.9 consisting of (70-80) on standard interpretation. The ability to learn qiraah after applying the Good Expert Group method of students is demonstrated by obtaining an average score of 89.5 consisting of (80-90) on standard interpretation. There is an increase in the ability to learn qiraah after applying the Expert Group method, which can be seen from the increase in the post-test by indicating the N-Gen of 0.69 or 69%. That is the increase in students' abilities in qiraah learning after applying the Expert Group method shows while in the interpretation of an interpretation.